Business Education, Institute of Business, and Entrepreneurship in Modern Russia - M. V. Markova; S. L. Sazanova (Управление)
The authors have revealed the interrelation of business education, institute of business, and entrepreneurship in modern Russia. The authors’ analysis of motivation for business schools’ prospective students has allowed reveal this motivation’s components, factors, stipulating the motivation, and the desire of business schools’ students to start the entrepreneurship. On the basis of theoretical and practical study the authors have justified practical recommendations aimed at enhancing of the business schools’ attractiveness for potential consumers.